2016
DOI: 10.3390/en9110883
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Coupled Dynamics of a Rod Fastening Rotor under Rub-Impact and Initial Permanent Deflection

Abstract: Abstract:A nonlinear coupled dynamic model of a rod fastening rotor under rub-impact and initial permanent deflection was developed in this paper. The governing motion equation was derived by the D'Alembert principle considering the contact characteristic between disks, nonlinear oil-film force, rub-impact force, unbalance mass, etc. The contact effects between disks was modeled as a flexural spring with cubical nonlinear stiffness. The coupled nonlinear dynamic phenomena of the rub-impact rod fastening rotor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Throughout the years, several works have been published on the subject of nonlinear rotor dynamics considering the bolted joint. Hu et al [23][24] developed the dynamic model of rod fastening rotor system, where the interaction between two disks was equivalent to a contact layer with nonlinear flexural stiffness. And then analyzed the bifurcation and chaos phenomena of the system under rub-impact and initial deformation of the shaft.…”
Section: Numerical and Experimental Analysis Of The Effect Of Eccentricmentioning
confidence: 99%
“…Throughout the years, several works have been published on the subject of nonlinear rotor dynamics considering the bolted joint. Hu et al [23][24] developed the dynamic model of rod fastening rotor system, where the interaction between two disks was equivalent to a contact layer with nonlinear flexural stiffness. And then analyzed the bifurcation and chaos phenomena of the system under rub-impact and initial deformation of the shaft.…”
Section: Numerical and Experimental Analysis Of The Effect Of Eccentricmentioning
confidence: 99%
“…It is according to the finite element analysis results of the force and deformation of the micro body element on the elastic-plastic rough surface, which improved the calculation accuracy. Hu et al [24][25][26] studied the nonlinear dynamic response of a two-disk rod fastening rotor with transverse crack, initial bending, rub impact and other faults, and analyzed the influence of system parameters such as speed, crack size, crack angle, contact surface damping coefficient, initial bending and rub impact stiffness on the dynamic characteristics. Li et al [27] studied the nonlinear dynamic characteristics of a three-disk bending torsional coupling rod fastening rotor under rub impact fault, concluded that the influence of torsional vibration on bending vibration gradually increases with the increase in rotating speed.…”
Section: Introductionmentioning
confidence: 99%
“…The bearing-rotor system is widely used in many rotating machineries, such as industrial compressors, steam turbines and aero engines. These shafts are usually composed of several sections which may not reach the proper design state due to structural characteristics or insufficient machining during the installation process [1,2]. As a result, the initial bending is inevitably generated and dynamic vibration of the rotor system is increased together with mass eccentricity.…”
Section: Introductionmentioning
confidence: 99%